Culture of entrepreneurship and innovation in the agri-food industry. An overall review - Silva Chuquipoma, Diego Honorato (2023)
The culture of entrepreneurship and innovation are synergistic elements that accompany business success at all levels, which have assumed a relevant role in the food industry, considered one of the sectors with contributions in health, nutrition and food worldwide. In this review article, the main cases and entrepreneurship factors were analyzed, as well as the most relevant innovation models in the global agri-food industry, for which a literary review was carried out, filtering and selecting 50 scientific articles published from 2017 to 2021. Subsequently, they were classified into subtopics according to the information obtained, facilitating their understanding and specific analysis. Finally, it is concluded that the main contributions to knowledge in entrepreneurship and innovation are focused on sustainable and profitable proposals in political, socio-cultural, environmental and technological fields as well as validation procedures, techniques and instruments for its application in the food industry. We also provide recommendations for future research directions in the food sector.